A component development method for vehicle body structure based on limited vehicle data. Issue 5 (5th October 2022) - Li, Danshi; Zhang, Fan; Lan, Jiebin; Klaas, Peter Jakob; Fang, Xiangfan
Abstract: Due to the reduction of vehicle development time and cost constraints, increasing volumes of vehicle development work are being transferred from automotive manufacturers to suppliers. In the area of vehicle structure development, one of the major challenges for suppliers is to deliver a good structural solution in a short time with very limited vehicle data. For those crash-relevant components or modules, such as the A- and B-pillar and the door module, considerable inaccuracies can be expected in the results when using partial vehicle data, as opposed to complete data, with the traditional component validation methods. In this work, a new component development method has been developed, and its implementable crash test bench for small vehicles has been virtually realised. This method focuses on the side impact tests at this phase, such as side impact with a mobile deformable barrier and a side pole impact. Reducing the number of required surrounding components and finding proper boundary conditions that can be implemented in the real test bench are the principle objectives of this work. The results of the crash simulations show a good correlation between the component sub-model and the full vehicle (FV) model using this method.